Effect of culling open cows on reproductive performance - Schalles, R.R.; Kiracofe, G. (Kansas State University. Agricultural Experiment Station, 2011)
The reproductive performance of a herd of Polled Hereford cows was evaluated over an eight year period. Culling cows the first time they were open would not have improved the future calving rates in this herd. The cost of replacing an open cow should be compared with the cost of maintaining an open cow. Thus, more improvement in reproduction can probably be made through good nutrition and management than by culling cows found open only once.
Keywords: Beef; Culling Cows; Reproductive performance; Open cows